2001
DOI: 10.1007/bf02490367
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of ten pine species from central portugal by monoterpene enantiomer-selective composition analysis using multidimensional gas chromatography

Abstract: SummaryThe composition of the volatile terpenes emitted by different trees has been successfully used as markers in a wide variety of studies such as chemotaxonomy. In this work discrimination among ten pine species, R pinea, R pinaster, R brutia, R elliottii, R halepensis, R kesiya, R radiata, R patula, R sylvestris, and R taeda was achieved by analyzing the relative composition of their volatile emissions. The analysis was performed after simultaneous distillation extraction; 16 monoterpenes were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Fischedick et al 16 discriminated varieties of Cannabis by GC, using the quantitative data for monoterpenoids, sesquiterpenoids and cannabinoids. Similar studies involving Pinus were reported previously, for different species than those studied here, based on chemical analysis of the volatiles produced by different tissues including needles, [17][18][19] seeds, 20 cones, 21 xylem 22,23 and phloem. 24 The application of chemometry in studies in Brazil was recently reviewed by Bruns et al 25 In the present study, it was collected and characterized the volatiles emitted by branches of five pine species cultivated in Brazil, P. elliottii, P. taeda, Pinus caribaea Morelet, Pinus maximinoi H. E. Moore and Pinus patula Schiede ex Schlechtendal et Chamisso, by means of aeration, GC-FID (gas chromatography using a flame ionization detector), GC-MS and hierarchical cluster (HCA) and principal component (PCA) analyses, as potential methods to be used in the differentiation of these species.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Fischedick et al 16 discriminated varieties of Cannabis by GC, using the quantitative data for monoterpenoids, sesquiterpenoids and cannabinoids. Similar studies involving Pinus were reported previously, for different species than those studied here, based on chemical analysis of the volatiles produced by different tissues including needles, [17][18][19] seeds, 20 cones, 21 xylem 22,23 and phloem. 24 The application of chemometry in studies in Brazil was recently reviewed by Bruns et al 25 In the present study, it was collected and characterized the volatiles emitted by branches of five pine species cultivated in Brazil, P. elliottii, P. taeda, Pinus caribaea Morelet, Pinus maximinoi H. E. Moore and Pinus patula Schiede ex Schlechtendal et Chamisso, by means of aeration, GC-FID (gas chromatography using a flame ionization detector), GC-MS and hierarchical cluster (HCA) and principal component (PCA) analyses, as potential methods to be used in the differentiation of these species.…”
Section: Introductionsupporting
confidence: 86%
“…P. elliottii is discriminated based on the contents of camphene (3), (-)-β-pinene (6) and (E)-caryophyllene (15). The strong influence of (+)-α-pinene for P. taeda and (-)-β-pinene for P. elliottii was observed by Gomes da Silva et al 17 in extracts from needles of Pinus from central Portugal. (12) and thymol methyl ether (14), and the larger amount of β-phellandrene (10).…”
Section: Principal Component Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…Several authors have referred that both biosynthesis and biogenesis of mono-and sesquiterpenes are genetic and species dependent [12,16]. The differences found in the emission patterns of the genus Pinus are reported to be mainly quantitative, allowing for interspecific discrimination [9][10][11][12]15].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on conifer monoterpene emissions used samples from foliage [8,9,11,16,[18][19][20][21][22], cortex tissue [12], seeds [10], cones [11], or bark volatiles emissions after insect oviposition induction [14,15]. In most of these studies, simultaneous destillation-extraction (SDE) methods were used to isolate the volatile compounds from the complex matrices [8,9,13,20,23,24].…”
Section: Introductionmentioning
confidence: 99%